Analysis of the Potential Threats of the West Papua National Coalition for Liberation (WPNCL) in the International Environment against the Integrity of the Unitary Republic of Indonesia - Fajar Dinar Putri Suseno; Margaretha Hanita (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The issue of Papua, especially related to the movement of the West Papua National Coalition for Liberation (WPNCL) in the international environment, is likely to have an impact on the integrity of the Republic of Indonesia. This was motivated by WPNCL's efforts in fighting for Papuan independence both at home and abroad. The theoretical basis used in this study refers to the theory of self-determination, the theory of separatism, and the theory of public diplomacy. This type of research is descriptive analytical, using qualitative data, through data collection methods from the literature and reference studies. This study explains that the Papuan problem has yet to find a common ground or solution in its resolution. In fact, due to the dissatisfaction of the Papuan people over the Act of Free Choice and differences in understanding about Papua's history, which is increasingly protracted, it has triggered the emergence of Papuan separatist movements at home and abroad. The political movement maneuver of the Papuan separatist groups in the international environment aims to represent the demands of self-determination in Papua. Issues raised in seeking support in the environment include reviewing the process of creating the New York Agreement, reviewing the results of the Act of Free Choice, and the high number of human rights violations in Papua. One of them is an independent Papuan organization that is involved in international propaganda activities, namely WPNCL, whose movement tends to focus on propaganda for Papuan issues in the international environment. Facing these conditions, the Government of Indonesia needs to establish a foreign policy to reduce the emergence of foreign interference in resolving Papuan problems and the movement of Papuan separatist groups. In conclusion, this study aims to analyze the potential threats from the WPNCL movement in the international environment that will have an impact on the integrity of the Unitary Republic of Indonesia.